Tracing the trajectory of vocational education research on career adaptability: a bibliometric study - Haryadi, Rudi; Abdullah, Ade Gafar; Widiaty, Isma (Journal of Education and Learning (EduLearn), 2024)
Reports on the evaluation of the most relevant themes on career adaptability through bibliometric analysis using the keyword “career adaptability” as its input aims to get a comprehensive view of current issues and trends in career adaptability research. The VOSviewer software in collaboration with Microsoft Excel and Open Refine was adopted as tool to visualize the network of authors, countries of origins and keywords in publication data mined on June 19 2022. The analysis found a total of 728 scientific publication from 1981 to 2022. The results show that in the last 15 years the number of career adaptability publications has grown very significantly. The United States is a major country contributing of publications. Author analysis presents Nota L as the most prolific author, while Savickas L is a prominent author while Guan Y is the writer with the best writing network with 8 other writers on career adaptability. Academic Press Inc. dominates the publication with 22.94% of it is production. Keyword analysis shows that career adaptability studies in the last two decades have focused on the theme of career planning through the establishment of a career guidance framework that aims to create prosperity.